1997
DOI: 10.1002/(sici)1096-9071(199706)52:2<200::aid-jmv14>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Quantity of cytomegalovirus viruria is a major risk factor for cytomegalovirus disease after renal transplantation

Abstract: Studies have shown that risk factors for human cytomegalovirus (HCMV) disease after renal transplant include primary infection (virus of donor origin infecting a non-immune individual), re-infection (virus of donor origin infecting a immune individual), and the detection of viraemia (as a marker of virus dissemination). We now report that viral load in the urine is also a significant factor in HCMV disease and is one of the main mechanisms underlying the risk associated with viraemia and donor serostatus. Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 23 publications
(31 reference statements)
4
41
0
Order By: Relevance
“…In similar studies we have identified threshold viral load levels for disease in the blood of liver transplant recipients, 20 and in the urine of renal transplant patients. 21 In conclusion, the data in this study demonstrate the central role of viral load in the pathogenesis of HCMV in the bone marrow transplant recipient and provide the mechanism by which previously identified risk factors are associated with disease. These data also provide a rational approach to reducing viral loads below critical levels through antiviral chemotherapeutic targeting of patients most at risk of symptomatic infection, as well as monitoring the success of such interventions.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In similar studies we have identified threshold viral load levels for disease in the blood of liver transplant recipients, 20 and in the urine of renal transplant patients. 21 In conclusion, the data in this study demonstrate the central role of viral load in the pathogenesis of HCMV in the bone marrow transplant recipient and provide the mechanism by which previously identified risk factors are associated with disease. These data also provide a rational approach to reducing viral loads below critical levels through antiviral chemotherapeutic targeting of patients most at risk of symptomatic infection, as well as monitoring the success of such interventions.…”
Section: Discussionsupporting
confidence: 53%
“…18 In other patient populations at risk of HCMV disease, quantification of HCMV load has provided another risk factor for HCMV disease. Specifically, cross-sectional and longitudinal studies have indicated the importance of monitoring HCMV load in congenitally infected infants, 19 renal transplant recipients [20][21][22] and HIV infected patients. 23,24 There is, however, a paucity of information on longitudinal fluctuations in cytomegalovirus load in the bone marrow transplant patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Seroepidemiological studies have shown that approximately 60% of adults in developed countries and up to 100% of adults in developing countries are positive for antibodies against HCMV. 5 BMT recipients negative for anti-HCMV antibody are at risk of primary infection. 5 In addition, reactivation of latent HCMV is responsible for significant morbidity and mortality in BMT recipients, and HCMV pneumonia has a high mortality rate in patients who have received an allogeneic marrow transplant.…”
mentioning
confidence: 91%
“…5 BMT recipients negative for anti-HCMV antibody are at risk of primary infection. 5 In addition, reactivation of latent HCMV is responsible for significant morbidity and mortality in BMT recipients, and HCMV pneumonia has a high mortality rate in patients who have received an allogeneic marrow transplant. The diagnosis of HCMV disease is complicated because of varying clinical presentations and inherent difficulties in diagnosis.…”
mentioning
confidence: 99%